An updated long‐term homogenized daily temperature data set for Australia. (8th June 2020) - Trewin, Blair; Braganza, Karl; Fawcett, Robert; Grainger, Simon; Jovanovic, Branislava; Jones, David; Martin, David; Smalley, Robert; Webb, Vanessa
Abstract: A new version of the long‐term Australian temperature data set, known as ACORN‐SAT (Australian Climate Observations Reference Network—Surface Air Temperature), has been developed. ACORN‐SAT includes homogenized daily maximum and minimum temperature data from 112 locations across Australia, encompassing the period from 1910 to the present, with 60 of the locations having data for the full 1910–2018 period. Homogenization is achieved using a percentile‐matching methodology with a number of improvements beyond practices used in previous versions, including more effective detection and removal of potentially inhomogeneous reference stations and an enhanced breakpoint detection methodology. Explicit corrections have also been introduced for a change in instrument screen size, whilst an assessment has found that the transition from manual to automatic instruments and changes in effective response time of automatic instruments have had a negligible impact on the data. Adjustments associated with documented site moves from in‐town to out‐of‐town locations are predominantly negative, particularly for minimum temperature, with other adjustments showing no strong bias towards either positive or negative values. The new data set shows slightly stronger warming (0.12°C per decade in mean temperature over the 1910–2016 period) than either the previous ACORN‐SAT version (0.10°C) or the unhomogenized gridded data (0.08°C), primarily due to more effective treatment of systematic moves of sites out of towns and the removal of a rounding bias in the version 1 methodology. Abstract : A new version of the long‐term Australian temperature data set, known as ACORN‐SAT, has been developed. ACORN‐SAT includes homogenized daily maximum and minimum temperature data from 112 locations across Australia (including the site shown, at Rutherglen), from 1910 to the present. The new data set shows slightly stronger warming (0.12°C per decade in mean temperature over the 1910–2016 period) than the previous ACORN‐SAT version (0.10°C) or the unhomogenized gridded data (0.08°C).